2011
DOI: 10.1073/pnas.1101315108
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale approach to link red blood cell dynamics, shear viscosity, and ATP release

Abstract: RBCs are known to release ATP, which acts as a signaling molecule to cause dilation of blood vessels. A reduction in the release of ATP from RBCs has been linked to diseases such as type II diabetes and cystic fibrosis. Furthermore, reduced deformation of RBCs has been correlated with myocardial infarction and coronary heart disease. Because ATP release has been linked to cell deformation, we undertook a multiscale approach to understand the links between single RBC dynamics, ATP release, and macroscopic visco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
161
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 163 publications
(169 citation statements)
references
References 37 publications
6
161
0
2
Order By: Relevance
“…The lack of membrane fluidity for high viscosity contrast is the key feature that controls RBCs' behavior. Besides shear thinning, several fundamental physiological phenomena have been analyzed under the assumption of membrane tank treading, such as vasoregulatory ATP release by RBCs in strong shear flows (32) or the formation of a few-micron-thick cell-free layer adjacent to the vessels walls that is responsible for the apparent viscosity drop with decreasing vessel diameter, the so-called Fåhraeus-Lindqvist effect (33). Our study questions the relevance of such droplet-like analogy for RBC dynamics to explain these phenomena and seeks to reexplore them both experimentally and theoretically for physiologically relevant viscosity and stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of membrane fluidity for high viscosity contrast is the key feature that controls RBCs' behavior. Besides shear thinning, several fundamental physiological phenomena have been analyzed under the assumption of membrane tank treading, such as vasoregulatory ATP release by RBCs in strong shear flows (32) or the formation of a few-micron-thick cell-free layer adjacent to the vessels walls that is responsible for the apparent viscosity drop with decreasing vessel diameter, the so-called Fåhraeus-Lindqvist effect (33). Our study questions the relevance of such droplet-like analogy for RBC dynamics to explain these phenomena and seeks to reexplore them both experimentally and theoretically for physiologically relevant viscosity and stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This group also showed that human erythrocytes exhibited mechanosensitive large conductance channel activity consistent with Panx1, and that red cells exposed to either high K + or hypotonic stress displayed enhanced ATP release and dye uptake, in a carbenoxolone-sensitive manner [150]. A number of studies followed indicating that pharmacological inhibitors of Panx1 reduced ATP release in a broad range of cells, including lung epithelial cells [151][152][153], hypoxic red cells [154][155][156], bovine ciliary epithelial cells [157], retina and trabecular meshwork (TM5) cells [158,159], skeletal muscle [160], taste bud cells [161], T lymphocytes [61,62,162], and human neutrophils [109]. Panx1 knockdown (siRNA or shRNA) reduced nucleotide release in hypotonic-stressstimulated airway epithelial cells [151,152], stretched cardiomyocytes [163], apoptotic T lymphocytes [162] and T cells undergoing HIV infection [164], TM5 cells [159], and astrocytes [165].…”
Section: Pannexinsmentioning
confidence: 99%
“…Our numerical results also suggest the possibility of utilizing fluid flows to deliver macromolecules (e.g., drugs) by gating MS channels reconstituted in liposomes in microfluidic platforms. bending force, membrane tension, and hydrodynamic force (27,28) leads to different vesicle dynamics.…”
mentioning
confidence: 99%